THEORETICAL AND DIDACTIC FOUNDATIONS OF THE DISTANCE EDUCATION SYSTEM - Shirinov Feruzjon Shuxratovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides information on the theoretical and didactic foundations of distance education and its organization.